2023
DOI: 10.1111/jon.13089
|View full text |Cite
|
Sign up to set email alerts
|

Intraarterial thrombolytics as an adjunct to mechanical thrombectomy in patients with basilar artery occlusion

Abstract: Background and Purpose There are limited data regarding safety and effectiveness of concurrent intraarterial thrombolytics as adjunct to mechanical thrombectomy in acute ischemic stroke patients with basilar artery occlusion. Methods We analyzed data from a prospective multicenter registry to assess the independent effect of intraarterial thrombolysis on (1) favorable outcome (modified Rankin Scale 0‐3) at 90 days; (2) symptomatic intracranial hemorrhage (sICH) within 72 hours; and (3) death within 90 days pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…A previous meta-analysis including 4581 patients by Chen et al 10 reported that IA treatment (thrombolytics or glycoprotein IIb/IIIa inhibitors) was associated with a higher rate of functional independence and another meta-analysis including 2797 patients by Kaesmacher et al 11 reported that IAT was not associated with higher rates of functional independence as an adjunct to MT. Inclusion of additional studies 5,[12][13][14][15][16][17] such as results from the randomized CHOICE 17 trial in our analysis increased the sample size (7572 patients) by almost 2-4 folds compared with the previous analyses by Chen et al 10 and Kaesmacher et al 11 Therefore, the precision of estimates of various outcomes was higher, and type 2 errors in comparisons were reduced. By increasing the design diversity among included studies, we also identified the prominent effect of design and quality of the studies on the association between IAT and functional independence at 90 days.…”
Section: Salient Findingsmentioning
confidence: 76%
See 3 more Smart Citations
“…A previous meta-analysis including 4581 patients by Chen et al 10 reported that IA treatment (thrombolytics or glycoprotein IIb/IIIa inhibitors) was associated with a higher rate of functional independence and another meta-analysis including 2797 patients by Kaesmacher et al 11 reported that IAT was not associated with higher rates of functional independence as an adjunct to MT. Inclusion of additional studies 5,[12][13][14][15][16][17] such as results from the randomized CHOICE 17 trial in our analysis increased the sample size (7572 patients) by almost 2-4 folds compared with the previous analyses by Chen et al 10 and Kaesmacher et al 11 Therefore, the precision of estimates of various outcomes was higher, and type 2 errors in comparisons were reduced. By increasing the design diversity among included studies, we also identified the prominent effect of design and quality of the studies on the association between IAT and functional independence at 90 days.…”
Section: Salient Findingsmentioning
confidence: 76%
“…The quality of included observational studies 5,6,[12][13][14][15][16][20][21][22][25][26][27][28][29][30][31] was assessed by three independent reviewers (A.L., I.N.A., and D.K.) for risk of bias using the Newcastle-Ottawa Quality Scale (NOS) for Cohort Studies.…”
Section: Risk Of Bias Assessment In Studiesmentioning
confidence: 99%
See 2 more Smart Citations